Unlocking Employee Performance: Knowledge Sharing, Motivation, and Innovation Dynamics: Peran Knowledge Sharing Enablers, Motivasi Kerja, dan Kemampuan Inovasi Individu terhadap Kinerja Pegawai - Pinata, Febby Tiara; Sumartik, Sumartik; Firdaus, Vera (Indonesian Journal of Innovation Studies, 2023)
This quantitative study investigates the intricate interplay between knowledge sharing enablers, motivation work behavior, individual innovation capability, and the performance of secretariat employees in the Sidoarjo Regency. The research, encompassing all 70 secretariat employees, employs a total sampling technique and utilizes Likert-scale questionnaires. Employing multiple linear regression analysis, the findings reveal that knowledge sharing enablers, motivation work behavior, and individual innovation capability significantly influence the performance of secretariat employees in the Sidoarjo Regency. This study sheds light on the pivotal roles of collaborative knowledge sharing, motivated work behavior, and individual innovation in enhancing the overall efficiency of secretariat operations, offering valuable insights for organizational development and human resource management in a global context. Highlights: Collaborative Dynamics: Explore the influence of knowledge sharing, motivation, and innovation capability on the performance of secretariat employees. Quantitative Analysis: Utilize multiple linear regression to unveil the significant impact of knowledge sharing enablers, motivation work behavior, and individual innovation capability. Global Relevance: Provide insights into enhancing secretariat operations with implications for organizational development and human resource management on a global scale. Keywords: Knowledge Sharing, Motivation, Innovation Capability, Employee Performance, Secretariat Operations